ChemInform Abstract: A Review of Anaerobic Membrane Bioreactors for Municipal Wastewater Treatment: Integration Options, Limitations and Expectations. Issue 50 (10th December 2013) - Ozgun, Hale; Dereli, Recep Kaan; Ersahin, Mustafa Evren; Kinaci, Cumali; Spanjers, Henri; van Lier, Jules B.
Abstract Review: 107 refs.